Evaluation of mixed-fermentation of Saccharomyces cerevisiae with Saprochaete suaveolens to produce natural fruity beer from industrial wort. (1st June 2021) - Tan, Melissa; Caro, Yanis; Shum-Cheong-Sing, Alain; Robert, Laurent; François, Jean-Marie; Petit, Thomas
Highlights: The yeast S. suaveolens has been tested for the natural flavoring of beer. In mixed-fermentation of wort S. suaveolens maintained an active aromatic metabolism. Wort inoculated with 30% of S. suaveolens produced beers with normal ethanol content. Wort inoculated with 90% of S. suaveolens produced beers with low-alcohol content. Beers produced with 30% of S. suaveolens were significantly enriched with aromas. Abstract: Fruity beers can be promoted through production of flavoring compounds during fermentation by partial replacement of brewing yeast by non-conventional-yeasts with high aroma production abilities. We evaluated here the use of a wild Saprochaete suaveolens strain, producing atypical aroma compounds, to produce new natural fruity beer, while keeping classical production conditions used in brewing industry. S. suaveolens was inoculated as starter of culture during beer fermentation and the fermentation performance was evaluated through measurement of several physicochemical parameters. The aroma profile of the engineered beers was monitored using HS-SPME GC/MS. The results showed that high fruity aroma and low-ethanol content beers were obtained through single-fermentation using S. suaveolens . We also demonstrated that during mixed-fermentation, S. suaveolens maintained high metabolic activity and allowed production of beer enriched with fruity aroma. Production of high or low ethanol content fruity beer could be achieved by varying the composition of the starter of culture.